Coexistent squamous cell carcinoma and tuberculosis in cervix - A rare occurrence - Raje, P; Bhandari, S (Journal of Pathology of Nepal, 2015)
Coexistence of squamous cell carcinoma cervix with tuberculosis cervix, as reported in literature, is a rare entity. Only 8 cases have been reported in the world literature so far. Tuberculosis in general is rampant in developing countries, especially in India, and so is carcinoma cervix and hence one would expect a much higher incidence of coexistence of two. However tuberculosis cervix is a rarely reported disease.We report a case of tuberculosis cervix associated with squamous cell carcinomaand regional lymph node involvement in a postmenopausal woman. Journal of Pathology of Nepal (2015) Vol. 5, 781-783